Pleistocene Stratigraphy of the Athabasca River Valley Region, Rocky Mountains, Alberta - Levson, Victor; Rutter, Nathaniel (Géographie physique et Quaternaire, 1995)
ABSTRACTThe Pleistocene stratigraphy of the central Canadian Rocky Mountains is described from a region where few studies of Late Quaternary deposits have been conducted. Six informal lithostratigraphic units are recognized from newly mapped exposures in Jasper National Park. The oldest deposits are interpreted as paleofan deposits (Unit 1) and they are overlain by glaciofluvial gravels and sands (Unit 2), glaciolacustrine sediments (Unit 3) and by a glacigenic diamicton sequence (Unit 4) that includes basal till, supraglacial deposits and ice-marginal debris flow sediments. Proximal glaciofluvial gravels, debris flow deposits and minor glaciolacustrine sediments (Unit 5) and paragiacial fan deposits and loess (Unit 6) cap the stratigraphic sequence. Limited chronologic control suggests that nonglacial fluvial and alluvial fan sedimentation began prior to 48 ka and continued throughout the Middle Wisconsinan. Braided stream deposits were accumulating in the Athabasca River valley near Jasper townsite about 29 ka. In the Late Wisconsinan, Rocky Mountain and Cordilleran glaciers advanced through the area, initially damming lakes in a number of Front Range tributary valleys. During déglaciation, ice-marginal glaciofluvial activity and paragiacial debris flows dominated sedimentation. Glacial lakes were limited in extent. A radiocarbon date on shells from one small ice-marginal lake indicates that glaciers were well in retreat by about 12 ka. Alpine glaciers in the region were at or near their present limits by 10 ka.